2014
DOI: 10.1155/2014/296498
|View full text |Cite
|
Sign up to set email alerts
|

Coating of Mesh Grafts for Prolapse and Urinary Incontinence Repair with Autologous Plasma: Exploration Stage of a Surgical Innovation

Abstract: Purpose. Optimized biocompatibility is a major requirement for alloplastic materials currently applied for stress urinary incontinence (SUI) and pelvic organ prolapse (POP) repair. In the preliminary studies the mesh modification by coating with autologous plasma resulted in the increased adherence score in vitro and improved biocompatibility in an animal model. The first use of plasma coated meshes in human is presented. Materials and Methods. Between 04/2013 and 05/2014, 20 patients with the indication for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…Besides in vitro and in vivo data, the method has already proven feasible in a pilot study with 20 patients, thereby diminishing safety concerns [21]. In addition, our group has already developed and successfully implemented a long-term register for meshes and mesh modifications [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides in vitro and in vivo data, the method has already proven feasible in a pilot study with 20 patients, thereby diminishing safety concerns [21]. In addition, our group has already developed and successfully implemented a long-term register for meshes and mesh modifications [22].…”
Section: Discussionmentioning
confidence: 99%
“…The current study protocol is based on the feasibility analysis of an already concluded successful pilot study with 20 patients [21]. Application of autologous blood plasma coating is performed according to the German Pharmaceutical Law (AMG), the Medical Product Act (MPG), and the Transfusion Act.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study design was applied to evaluate the feasibility of the registry. Different mesh materials were used (TVT ® , Seratim ® , Ultrapro ® , Vitamesh ® ) and were all modified by a new technique with preoperative surface coating with autologous plasma [12]. The technique has been evaluated previously in accordance with preclinical IDEAL stage 0 [13].…”
Section: Patientsmentioning
confidence: 99%